2012
DOI: 10.1097/qad.0b013e328354b43f
|View full text |Cite
|
Sign up to set email alerts
|

Chronic progressive HIV-1 infection is associated with elevated levels of myeloid-derived suppressor cells

Abstract: We conclude that chronic uncontrolled HIV-infection is associated with elevated levels of MDSC, which potentially contribute to the impaired T-cell responses characteristic for the progressive disease stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
185
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(201 citation statements)
references
References 18 publications
14
185
2
Order By: Relevance
“…Vollbrecht et al (2012) showed that chronically HIV-infected HAART-naive individuals had significantly higher MDSC levels than healthy controls which was positively correlated with the viral load and negatively correlated with CD4 + T cell count. Qin et al (2013) found a significant increase of MDSCs in HIV-1-seropositive patients in comparison with healthy controls even in the presence of efficient anti-retroviral therapy.…”
Section: Mdscs As a Target For Diseases Of Ageingmentioning
confidence: 97%
“…Vollbrecht et al (2012) showed that chronically HIV-infected HAART-naive individuals had significantly higher MDSC levels than healthy controls which was positively correlated with the viral load and negatively correlated with CD4 + T cell count. Qin et al (2013) found a significant increase of MDSCs in HIV-1-seropositive patients in comparison with healthy controls even in the presence of efficient anti-retroviral therapy.…”
Section: Mdscs As a Target For Diseases Of Ageingmentioning
confidence: 97%
“…Beyond P. aeruginosa, these findings may have a broader relevance for infections with flagellated bacteria in general, such as Helicobacter pylori, Salmonella typhimurium, or flagellated Escherichia coli strains. The flagellin-induced upregulation of the G-protein-coupled receptor CXCR4 on MDSCs could pave the way to target this leukocyte subset pharmacologically, using small-molecule inhibitors and underpins, with CXCR4 as HIV coreceptor, a potential role for MDSCs in HIV infection (50). Our observation that flagellin induced CXCR4 high MDSCs, but that CXCR4 was dispensable for MDSC-mediated T cell suppression, may further suggest that CXCR4 in this setting may play a role in MDSC functionality beyond T cell suppression, such as MDSC migration, homing, or survival.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has demonstrated that MDSCs were closely associated with disease progression in malignancy and some inflammation-mediated pathological conditions (7,16). Although recent studies report MDSC expansion in viral infections (17)(18)(19)(20)(21)(22), phenotypic and functional features of MDSCs are still poorly defined in patients with CHB. The aim of this study was to determine whether MDSCs are involved in the impaired immune response leading to chronic HBV infection.…”
Section: Hla-drmentioning
confidence: 99%